An ab-initio study of H2O adsorption on the calcite (104) surface with different coverages. (June 2020) - Zhao, Jian; Wang, Jiamin; Qin, Xinzhan; Cao, Yu
Abstract: Calcite is the most important component of limestone, an essential building material. When adsorbing water, the strength of calcite decreases, resulting in safety problems. Density functional theory (DFT) is widely used to elucidate the adsorption mechanisms of calcite surface at a molecular level. The adsorption structures and energies of H2 O on calcite (104) surface were studied systematically for a wide coverage from 0 to 1.0 monolayers. The results show that a hollow site on calcite (104) surface is the most favorable when adsorbing H2 O with an energy of 0.89 eV, followed by 0.71 eV at the bridge site and 0.64 eV at the top site, i.e., water molecules are easily adsorbed on calcite surface. Besides, the changes in the atomic structure, density of electronic states, and charge distribution of H2 O/calcite (104) system before and after adsorption are discussed in detail for different coverages. Highlights: Density functional theory is used to investigate the interaction mechanism of H2 O and calcite at the molecular level. Three types of adsorption sites have been considered when water molecules adsorb on calcite (104) surface. The adsorption structures and energies of H2 O on calcite (104) surface are studied systematically for a wide coverage of 0 < Θ ≤ 1.0 monolayers (ML). The change of lattice relaxation and electronic structure of H2 O/calcite (104) system have also been discussed for different coverages.